Purification and partial characterization of peroxidases from three food waste by-products: broad bean pods, pea pods, and artichoke stems - MEJRI, Faiza (2019)
In this study, peroxidases (PODs) from three waste by-products: broad bean pods (BBP), pea pods (PP), and artichoke stems (ARS) were purified and their optimal conditions were determined for the first time. The purification process resulted in 4.32, 7.21, and 8.9% of POD recoveries for PP, ARS, and BBP, respectively. They were purified 2.12-, 32.97-, and 10-fold with specific activities of 27.26, 266.43, and 27 U/mg of protein, respectively. Analysis of their optimal conditions showed that POD purified from BBP and PP exhibited the highest activity at 60 degrees C temperature and pH 6 and 8 with strong affinity with catechol substrate (Km of 0.356 and 0.189 mM; Vmax of 0.08 and 0.041 mu M/min for BBP and PP, respectively). The highest activity of ARS POD was obtained under the following conditions: temperature at 50 degrees C, pH from 6 to 8, and guaiacol as substrate (Km 0.375 mM; Vmax 0.012 mu M/min). Apart from giving the opportunity for recycling the food industry wastes, the studied waste by-products could represent an alternative source of PODs that could find several applications in the biotechnological, chemical, and food industries.